1992
DOI: 10.1002/bjs.1800791141
|View full text |Cite
|
Sign up to set email alerts
|

General surgery in patients aged 80 years and older

Abstract: This study reviews 594 surgical admissions, of patients aged 80 years and older, to departments of general surgery during 1 year. Half of the patients were admitted as emergencies and 60 per cent underwent surgery. The operative mortality rate was 8 per cent and the overall mortality rate for all admissions 9 per cent. The number of complications and the mortality rate after surgery increased in emergency cases and in patients with coexisting disease. Of all admissions, 72 per cent were uncomplicated and in 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
17
0
4

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 6 publications
6
17
0
4
Order By: Relevance
“…It is well demonstrated that if postoperative 30-days mortality increases with the age, the presence and the number (two or more) of co-morbid disease is more important than chronological age as a risk factor; elderly patients without co-morbid conditions does not carry a substantial increased mortality risk [2][3][4]7,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well demonstrated that if postoperative 30-days mortality increases with the age, the presence and the number (two or more) of co-morbid disease is more important than chronological age as a risk factor; elderly patients without co-morbid conditions does not carry a substantial increased mortality risk [2][3][4]7,13].…”
Section: Discussionmentioning
confidence: 99%
“…As the elderly population grows, more than 50% of all hospitalized patients will be of geriatric age [1][2][3]. Because of it, rectal cancer shows a high incidence in older patients and radical surgical resection remains the most effective treatment; therefore, many studies on the shortand long-term outcome of surgery in the elderly have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…We found that postoperative complications and mortality in patients aged 80 years and older undergoing emergency surgery were 2.5 times higher than in those aged 65-79 years. Reports 12,13 indicate that mortality in the elderly undergoing emergency surgery is almost three times higher than in those undergoing elective surgery. Among operative factors, systemic abnormalities do not present typical symptoms as they do in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…In times of an ever ageing population, the numbers of patients with multiple medical co-morbidities presenting to the general surgical 'take' having suffered a catastrophic surgical event,are likely to increase. 1,2 Surgical intervention, with little hope of a cure, a return to independent living or an acceptable quality of life, may lead to unnecessary end-of-life suffering for the patients and their relatives, and consumes significant financial resources.…”
mentioning
confidence: 99%